THE INFLUENCE OF INNOVATION CULTURE AND STRATEGIC PLANNING, MEDIATED BY TECHNOLOGY ACQUISITION, ON THE COMPETITIVENESS OF THE INDONESIAN DEFENSE INDUSTRY - Sriyanto (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This research highlights the critical role of innovation culture and strategic planning in boosting the competitiveness of the Indonesian defense industry, primarily through the mediation of technology acquisition. Our findings confirm that a robust innovation culture positively and significantly influences technology acquisition, which in turn profoundly impacts the defense industry's competitiveness. Similarly, effective strategic planning positively and significantly contributes to technology acquisition, and while its direct effect on competitiveness isn't significant, its indirect influence via technology acquisition is crucial. Despite a growing defense budget, Indonesia's continued reliance on imported defense equipment underscores the need for enhanced domestic industry competitiveness. Therefore, fostering a strong innovation culture and strategic planning focused on technology acquisition is vital for achieving national defense industry self-reliance and competitiveness